Stres Akademik Mahasiswa dalam Pembelajaran Daring pada Masa Pandemi Covid-19 di Universitas Katolik Widya Mandala Surabaya Kampus Kota Madiun - Mudjijanti, Fransisca (Jurnal Konseling Komprehensif: Kajian Teori dan Praktik Bimbingan dan Konseling, 2021)
This study aims to obtain an overview of academic stress levels among students of UKWMS Madiun due to online learning during Covid-19 pandemic. The research method used in this study is descriptive quantitative method, with data collection technique using questionnaire in the form of scale. The population of this study were all 777 active students of UKWMS Madiun in the academic year of2020/2021. The research samples of this study were 220 students, determined by using Isaac and Michael table. The results of this study showed that stress levels among UKWMS Madiun students are 47% experienced mild academic stress, 50% experienced moderate academic stress, and 3% experienced severe academic stress.